Genetic Diversity of Polymorphic Marker Merozoite Surface Protein 1 (Msp-1) and 2 (Msp-2) Genes of Plasmodium falciparum Isolates From Malaria Endemic Region of Pakistan - Khan, Shahid Niaz; Ali, Rehman; Khan, Sanaullah; Rooman, Muhammad; Norin, Sadia; Zareen, Shehzad; Ali, Ijaz; Ayaz, Sultan (Frontiers in Genetics, 2021)
Background: Understanding the genetic diversity of Plasmodium species through polymorphic studies can assist in the designing of more effective control strategies of malaria like new drug formulation and development of a vaccine. Pakistan is moderate endemic for Plasmodium falciparum, but little is known about the genetic diversity of this parasite. This study aimed to investigate the molecular diversity of P. falciparum based on msp-1 and msp-2 in the malaria-endemic regions of the Khyber Pakhtunkhwa, Pakistan. Methods: A total of 199/723 blood samples, tested positive by microscopy for falciparum malaria, were collected from four districts (Dera Ismail Khan, Karak, Mardan, and Peshawar) of the Khyber Pakhtunkhwa. Nested Polymerase Chain Reaction (PCR) amplification technique was employed to target the block 2 of msp-1 and the central domain of msp-2 genes, including their respective allelic families K1, MAD20, RO33, and FC27, 3D7/IC and detect the extent of genetic diversity of P. falciparum clinical isolates. Results: Among the (n=199) microscopy positive P. falciparum samples, a total of (n=192) were confirmed using PCR. Ninety-seven amplicons were observed for msp-1 and 95 for msp-2. A total of 33 genotypes, seventeen for msp-1 (8 K1; 6 MAD20; 3 RO33) and sixteen for msp-2 (9 FC27; 7 3D7/IC), were identified. The specific allelic frequency of the K1 family was higher (44.3%) than MAD20 (33.0%) and RO33 (23.0%) for msp-1, ¬while the FC27 allelic family was dominant (60%) than 3D7/IC (40%) for msp-2. No polyclonal infection was observed in msp-1 and msp-2. The expected heterozygosity was 0.98 and 0.97 for msp-1 and msp-2, respectively. Conclusion: It was concluded that the P. falciparum populations are highly polymorphic and diverse allelic variants of msp-1 and msp-2 are present in the Khyber Pakhtunkhwa, Pakistan.